2005
DOI: 10.1071/mf04221
|View full text |Cite
|
Sign up to set email alerts
|

Recent growth rate of larval pilchards Sardinops sagax in relation to their stable isotope composition, in an upwelling zone of the East Australian Current

Abstract: The recent growth rate and stable isotope composition of larval pilchards, (Sardinops sagax, 6-29 mm standard length), captured in surface and near-surface waters, were examined in coastal upwelling and non-upwelling regions of the EastAustralian Current over two cruises during the austral summer of 1998/1999. Compared to the nonupwelled regions, larvae were larger in the upwelling regions, and yet the back-calculated recent growth over 2 days before capture was significantly less on both cruises. This surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
16
2
Order By: Relevance
“…T. novaezelandiae is more associated with EAC water than S. sagax and is likely to have a spring spawning distribution similar to S. australasicus (Syahailatua et al 2011a,b). Together these species occur as larvae during spring on the continental shelf and are observed in near-shore upwelling zones (Uehara et al 2005;Syahailatua et al 2011b) or 200 km offshore in the Tasman Front (Condie et al 2011;Mullaney et al 2011). The co-occurrence of these species within the eddy indicates mixing of shelf and EAC water prior to eddy formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T. novaezelandiae is more associated with EAC water than S. sagax and is likely to have a spring spawning distribution similar to S. australasicus (Syahailatua et al 2011a,b). Together these species occur as larvae during spring on the continental shelf and are observed in near-shore upwelling zones (Uehara et al 2005;Syahailatua et al 2011b) or 200 km offshore in the Tasman Front (Condie et al 2011;Mullaney et al 2011). The co-occurrence of these species within the eddy indicates mixing of shelf and EAC water prior to eddy formation.…”
Section: Discussionmentioning
confidence: 99%
“…RGI was calculated as the mean daily growth (mm) of the last three full days of life divided by the natural log of the standard length (Uehara et al 2005). This removed any relationship between growth and size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10(a)], however, indicates an increasing δ 15 N trend, which demonstrates that larvae undergo ontogenetic development. δ 15 N enrichment linked to trophic shifts has been described in the Pacific sardine S. sagax and the Japanese anchovy Engraulis japonicus Temminck & Schlegel 1846 (Lindsay et al , 1998; Uehara et al , 2005). An increase in the variance of δ 15 N has been ascribed to a broader niche width in fish larvae (Malzahn & Boersma, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Watanabe & Kuroki (1997) reported allometric R O and L T relationships for larvae collected offshore of the Kuroshio Current (range: 6–21 mm L T ) and in coastal waters (range: 18–34 mm L T ). In addition, Uehara et al , (2005) reported slightly allometric R O and L T relationships for larval Sardinops sagax (Jenyns) in pre‐upwelling and upwelling regions in the East Australian Current (range: 6–26 mm L T ). This evidence along with the results of the current study suggests that the otolith size–larval size relationship based on observed age‐on‐length data become asymptotic at the end of the larval stage.…”
Section: Discussionmentioning
confidence: 99%